2017
DOI: 10.1021/acs.orglett.7b02771
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Synthesis of 1H-Indenes and Phthalimides via Isocyanide Insertion

Abstract: A new and versatile multicomponent domino strategy has been developed for the synthesis of a series of 1H-indene and phthalimide derivatives from simple and readily available starting materials. This process operating under mild conditions shows a broad substrate scope with moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…As versatile organic synthons, isocyanides have been applied to various transformations. Our group also carried out a series of studies on their C1 uses in transition-metal-catalyzed reactions, radical reactions and ionic reactions . The use of isocyanides as diatomic building blocks was also developed with transition-metal catalysts such as Ag and Cu, ,, Lewis acids, and metal-free conditions to generate new chemical bonds with both C and N atoms.…”
mentioning
confidence: 99%
“…As versatile organic synthons, isocyanides have been applied to various transformations. Our group also carried out a series of studies on their C1 uses in transition-metal-catalyzed reactions, radical reactions and ionic reactions . The use of isocyanides as diatomic building blocks was also developed with transition-metal catalysts such as Ag and Cu, ,, Lewis acids, and metal-free conditions to generate new chemical bonds with both C and N atoms.…”
mentioning
confidence: 99%
“…Finally, the compatibility with tertiary, secondary, and primary isocyanides is high, but no further investigations into the isocyanide scope were performed. The same group later reported a similar transformation to phthalimides from o-bromobenzonitriles [117]. In the same year, it was reported that maleimides 260 can be synthesized via a similar oxidative double imidoylation of internal alkynes 163 affording the corresponding maleimides 260 in good yields (Scheme 68) [116].…”
Section: Scheme 65mentioning
confidence: 92%
“…Finally, the compatibility with tertiary, secondary, and primary isocyanides is high, but no further investigations into the isocyanide scope were performed. The same group later reported a similar transformation to phthalimides from o-bromobenzonitriles [117]. Follow-up chemistry using this reaction involved the trapping of the transient yniminyl palladium species with carboxylates (Scheme 69) [118].…”
Section: Scheme 65mentioning
confidence: 96%
See 1 more Smart Citation
“…One more example of Pd catalyzed synthesis of indenes was studied by Wu and Jiang using 2‐(2‐bromophenyl)acetonitriles 89 , isocyanides 90 and amines 91 , as starting materials. The multicomponent reaction proceeds through a migratory insertion of isocyanides under mild conditions and displays wide functional group compatibility (Scheme ).…”
Section: Transition Metal (Tm)‐catalyzed Processesmentioning
confidence: 99%